Availability and quality of medical services in Ukraine under martial law conditions: aspects of management - Khozhylo, Iryna; Lipovska, Nataliia (My University, 2022)
The article investigates special features of health care policies under martial law conditions. It determines that the national model of the health care system management has been in an active phase of the medical reform since 2015. The reform covers about 20,000 health care facilities. Under COVID19 pandemic conditions, the national model of health care management operates on the principles of synchronous action of all entities at all levels of management. In the conditions of the full-scale war, since February 24, 2022, the national model of the health care system has undergone structural and functional changes and its facilities operate as critical infrastructure institutions in an asynchronous mode. The health care institutions management in an asynchronous mode is mainly entrusted to local self-government bodies, and ensuring the sustainability of medical institutions depends on the operational situation in the area where medical institutions are located. At the central level of branch administration, a number of measures of legal, economic and organizational support for the implementation of Ukraine’ state policy aimed at the availability and quality of medical care under martial law conditions have been introduced.
Keywords: public management and administration; health care; Ukrainian state; medical institutions